PETA MOBILISASI SUARA POLITIK MASYARAKAT DESA SONGAN DALAM PEMILIHAN UMUM KEPALA DAERAH KABUPATEN BANGLI TAHUN 2015 - Guntari, Ni Wayan Henny; Erviantono, Tedi; Amanda Gelgel, Dr.Ni Made Ras (Jurnal Nawala Politika, 2016)
ABSTRACT Bangli as one of the participating districts, regional head elections in 2015 in the province of Bali. Songan village is a village in the district of Kintamani Bangli regency. In 2015 Village Songan into one of the two actors participating in the election battle in gaining the support of the community in the area around Lake Batur. The theory used is the Theory of Democracy and the Theory of Capital were utilized two political actors in the General Election in the village of Bangli Songan. The method used is a qualitative exploratory. In this study found that the competition of two actors in the General Election in the village of Bangli Songan which raises two network utilization of capital which kinship networks and network state apparatus. Their kinship deployment, deployment over the state apparatus and there is a touch of the economic approach as a combination of capital used to mobilize the villagers Songan voice. So this research see that how these two political actors are able to utilize the capital that has been held in Bangli Election fight in 2015, especially in the village of Songan. The need for attention and action from the public and Bangli Election Commission in monitoring the implementation of the next election in the village Songan and Bangli.   Keywords: Village Election Songan, Mobilization Community Voice, Theory of Capital